Ekosistemska vloga, pomen in vplivi prostoživečih prežvekovalcev - Pokorny, Boštjan (Gozdarski vestnik, 2017)
In Europe, there are about 15 million individuals of wild ruminants (with a total biomass of 610,000 tons), belonging to 20 species; ten of them are indigenous (in Slovenia: European roe deer, red deer, and Alpine chamois), and ten are alien (in Slovenia: fallow deer, mouflon, and Alpine ibex). Although some subspecies are rare and/ or endangered, spatial distribution and abundance of the majority of species of wild ungulates (ruminants and wild boar) have increased all over Europe in the last years, which results in several challenges and opportunities in population management. Despite some conflicts, e.g. damage on agricultural land, impacts (and also damage) in forests, and increasing number of collisions with vehicles, wild ungulates are an important renewable natural and economical resource (e.g. high quality venison, source of hunting tourism), they have an important non- -consumptive (e.g. cultural, aesthetic, recreational) value, and as key species they have an important impact on biodiversity and development of terrestrial ecosystems. Among others, they provide several important ecosystem services as follows: creation of more heterogeneous habitats and long-term increase of biodiversity, impact on cycling and spatial mobility of nutrients, spreading of plant seeds (zoohory), and they also represent an important prey species for large carnivores and scavengers. Due to the mentioned roles they are important environmental engineers and an integral, vital part of both ecosystems and their management. Presence, distribution, and abundance of wild ungulates/ruminants should therefore be considered as an opportunity and important renewable natural resource rather than a disturbance, and populations should be managed with regard to the changing natural and social environment.
Keywords: prostoživeči parkljarji; wild ungulates; prežvekovalci; ruminants; red deer; navadni jelen; European roe deer; evropska srna; ecological role; ekosistemska vloga; population management; upravljanje populacij